Kristeva reframed interpreting key thinkers for the arts - Barrett, Estelle (London I.B. Tauris, 2011)
For Kristeva, in a world immersed in readymade images, art or aesthetic experience is a practice that constitutes both a subject (a sense of self) and an object that is able to transform meaning and consciousness. 'Kristeva Reframed' examines key ideas in Kristeva's work to show how they are most relevant to artists, and how they can be applied in interpreting artworks. With examples from the paintings of Van Gogh and Picasso, the work of contemporary feminist painters, the photography of Bill Henson and the film and animation work of Van Sowerine, Estelle Barrett demonstrates how Kristeva can.
Ch. 1. Language as material process -- Ch. 2. Interpretation as practice -- Ch. 3. Art and affect -- Ch. 4. Abjection, art and audience -- Ch. 5. Research as practice: a performative paradigm.
Includes bibliographical references (pages 151-157) and index.
Keywords: Kristeva, Julia -- 1941-.; Art and philosophy; Art and society; Electronic books